Cholesterol, triglycerides, HDL, and nitric oxide as determinants of resting heart rate variability in non-hospitalized mild post-COVID individuals: a cross-sectional study - Lucivalda Viegas de Almeida; Aldair Darlan Santos-de-Araújo; Luís Cláudio Nascimento da Silva; Patricia Martins Santos; Mariana Campos Maia; Victória Pereira Frutuoso; Daniel Santos Rocha; Adriana Sousa Rêgo; Daniela Bassi-Dibai (BMC Cardiovascular Disorders, 2025)
Abstract Background The association between plasma lipids, nitric oxide (NO) and cardiovascular risk has been well documented in the literature, however, the association between these outcomes and heart rate variability (HRV) in COVID-19 remains incipient as there is no scientific evidence that has investigated this outcome. Objective Investigate whether metabolic outcomes may be associated with cardiac autonomic behavior arising from short-term HRV variables in non-hospitalized mild post-COVID individuals. Methods This is a cross-sectional study. Individuals of both sexes, aged ≥ 18 years, who tested positive for SARS-CoV-2 according to the RT-PCR test, without the need for hospitalization, were included. The HRV was collected in the supine position for at least 10 min for later analysis in the Kubios software. Metabolic outcomes [high density lipoprotein (HDL) (mg/dL), cholesterol (mg/dL), triglycerides (mg/dL) and NO (µmol/L)] were collected through a blood sample. Results Seventy-three individuals were included (post-COVID = 32; control = 41). HRV was worse in the post-COVID group when compared to the control group (p < 0.05). Cholesterol, HDL, triglycerides and NO showed significant correlations with HRV indices. Regression models indicated that cholesterol and triglycerides, as well as NO, explain up to 30.3% of the variations in certain HRV indices, suggesting an impact of metabolic outcomes on autonomic modulation. Conclusion There is a relationship between plasma lipids, NO and HRV in non-hospitalized individuals with mild COVID-19. Metabolic outcomes are associated and explain between 16.6% and 30.30% of certain variables of resting HRV in post-COVID individuals. Clinical trial number Not applicable.